Hydromorphone population pharmacokinetics in pediatric surgical patients. Issue 10 (29th August 2020) - Balyan, Rajiv; Dong, Min; Pilipenko, Valentina; Geisler, Kristie; Vinks, Alexander A.; Chidambaran, Vidya
Abstract: Background: Hydromorphone is an opioid agonist used for pediatric analgesia. Due to lack of data, pediatric dosing (based on adult pharmacokinetic models) is not optimal. Aim: This study characterizes hydromorphone population pharmacokinetics in pediatric surgical patients. Methods: In this prospective observational study, 34 children (4‐18 years, bodyweight 23‐89.6 kg) received multiple intravenous hydromorphone boluses followed by postoperative hydromorphone patient‐controlled analgesia. Arterial blood samples were collected before and at 3, 10, 30, and 90 (and few samples at 1350) minutes after the first dose. Hydromorphone concentrations were measured by validated LC‐MS/MS assay. Nonlinear mixed‐effects modeling was used for pharmacokinetic model development. The final population pharmacokinetic model was evaluated by visual predictive check and bootstrap analysis. Monte Carlo simulations based on the final pharmacokinetic model determined optimal patient‐controlled analgesia parameters to achieve a target of 20 ng/mL (as the median effective analgesic concentration), using minimum effective analgesic concentration of 4 ng/mL as a proxy for patient‐controlled analgesia dose demand, and not exceeding the defined safe upper threshold of 40 ng/mL. Results: Hydromorphone pharmacokinetic profiles were adequately described by a two‐compartmental model with first‐order elimination. Bodyweight was found to be a significant covariate for hydromorphone clearance. Allometrically scaledpharmacokinetic parameter estimates (per 70 kg), systemic clearance (0.748 L/min), volume of distribution (33 L), peripheral clearance (1.57 L/min), and peripheral volume of distribution (146 L) were similar to reported adult parameter estimates. Sex, race, age, and type of surgery were not identified as significant covariates. To identify optimal patient‐controlled analgesia dosing parameters, we simulated several initial loading doses, demand doses, and lockout intervals. Our simulations support an initial patient‐controlled analgesia loading dose of 15 µg/kg followed by a demand dose of 6 µg/kg with lockout intervals of 20 minutes. Conclusions: After intravenous hydromorphone, plasma pharmacokinetic profiles in children undergoing different surgeries were well described by a two‐compartment population allometric pharmacokinetic model using bodyweight as the size descriptor. Model informed simulations identified patient‐controlled analgesia parameters to inform initial settings, with adjustments as needed based on observed individual effects.